Tumor Dormancy and the Angiogenic Switch: Possible Implications of Bone Marrow- Derived Cells - Shaked, Yuval; McAllister, Sandra; Fainaru, Ofer; Almog, Nava (Current Pharmaceutical Design, 2014)
Although escape from tumor dormancy has long been recognized as an important problem in the treatment of cancer, the molecular and cellular regulators underlying this transition remain poorly understood. The inability of the cancer cells to induce a complete and successful process of angiogenesis can result in tumor dormancy. In this case, the acquisition of sufficient angiogenic potential will result in the escape from indolence and in the initiation of tumor mass expansion. This stage in disease progression is known as the angiogenic switch. It is now becoming clear that the induction of the angiogenic switch is controlled by dynamic and complex biological processes involving the cancer cells, the associated stromal microenvironment and distant normal host cells, mostly from the bone marrow. Indeed, intricate tumor-host interactions are increasingly recognized as critical features of cancer. In particular, infiltrating cells of the immune system are crucial constituents of tumors and an important source of the growth stimulatory signals to the tumor cells. Tumor cells are surrounded by stromal cells, such as fibroblasts, lymphocytes, neutrophils, macrophages and mast cells, which communicate via a complex network of intercellular signaling pathways, mediated by surface adhesion molecules, cytokines and their receptors. However, the possible roles of these cells and molecules in the maintenance of micro-tumors in an occult state and in the induction of exit from the dormant state are not fully elucidated. In this review, we summarize recent findings and the current understanding of the role of bone marrow-derived cells, their recruitment into tumors and their interactive crosstalk with tumor cells, in leading to either the maintenance of, or exit from, tumor dormancy. Understanding the mechanisms of tumor growth and metastatic recurrence after periods of indolence is crucial for improving early detection, as well as increasing the cure rate for cancer patients.
Keywords: bone marrow-derived cells